Polymer waste management - Fink, Johannes Karl (John Wiley & Sons ; Scrivener Publishing, 2018)
With the huge amount of plastics floating in the oceans, fish and other sea creatures are directly suffering the consequences. On land, city leaders and planners are banning one-use plastics as well as plastic bags from grocery stores in an effort to stem the use. Many countries have made official announcements and warnings concerning the pollution caused from plastic wastes. These urgent developments have stimulated the author to study the problem and write Polymer Waste Management. Plastic recycling refers to a method that retrieves the original plastic material. However, there are many sophisticated methods available for the treatment and management of waste plastics such as basic primary recycling, where the materials are sorted and collected individually. In chemical recycling, the monomers and related compounds are processed by special chemical treatments. Other methods, such as pyrolysis, can produce fuels from waste plastics. These methods and others are treated comprehensively in the book This ground-breaking book also discusses: -General aspects, such as amount of plastics production, types of waste plastics, analysis procedures for identification of waste plastic types, standards for waste treatment, contaminants in recycled plastics.-Environmental aspects, such as pollution in the marine environment and landfills.-The advantages of the use of bio-based plastics.-Recycling methods for individual plastic types and special catalysts.